ANALYZING THE EFFECT OF MOTIVATION, LEADERSHIP STYLE, AND PERCEIVED WORKLOAD, WITH THE MODERATING EFFECT OF LEADERSHIP TO THE TEACHER’S COMMITMENT - Purnamasari, Dian; Firdaus, Robby Anzil; Akuba, Stefy Falentino (Dinasti International Journal of Management Science, 2020)
This article will analyze the effect of motivation, Leadership and perceived workload with the moderation effect of leadership to the teacher’s commitment. We use Structural Equation Modeling with descriptive quantitative analyzing. Samples were taken from a private Islamic school in Tangerang Selatan Indonesia, using census method to all the 61 teachers. The instrument is questionnaire using likert scales. Based on the results, motivation, Leadership and perceived workload with the moderation effect of leadership all together effecting 47.9% of teacher’s commitment. The result suggested that it is important to improve the leaders (principles or headmasters) leadership capability in order to get high commitment teacher. Leadership holds an important key for commitment.